2015
DOI: 10.1210/jc.2015-2198
|View full text |Cite
|
Sign up to set email alerts
|

Lower Preprandial Insulin and Altered Fuel Use in HIV/Antiretroviral-Exposed Infants in Cameroon

Abstract: HEU-A and HEU-N infants have lower preprandial insulin levels at 6 weeks of age and appear to use metabolic fuel substrates differently than HUU infants. Future studies are warranted to determine whether observed differences have lasting metabolic implications, such as later insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 38 publications
0
22
1
Order By: Relevance
“…As previously described, [13] we used PCA to consolidate and reduce the total number of AC and BCAA metabolites into a smaller number of uncorrelated variables/components. In general, PC1 was comprised of long-chain ACs and free carnitine (C0), PC2 of 3-hydroxy long-chain ACs, PC3 of short-chain and BCAA-related ACs, PC4 of unsaturated medium- and long-chain ACs, PC5 of BCAAs, PC6 of adipoyl/3-methylglutarylcarnitine (C6-DC) and dodecanoylcarnitine (C12) ACs, and PC7 of medium-chain ACs and tetradecenoylcarnitine (C14:1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As previously described, [13] we used PCA to consolidate and reduce the total number of AC and BCAA metabolites into a smaller number of uncorrelated variables/components. In general, PC1 was comprised of long-chain ACs and free carnitine (C0), PC2 of 3-hydroxy long-chain ACs, PC3 of short-chain and BCAA-related ACs, PC4 of unsaturated medium- and long-chain ACs, PC5 of BCAAs, PC6 of adipoyl/3-methylglutarylcarnitine (C6-DC) and dodecanoylcarnitine (C12) ACs, and PC7 of medium-chain ACs and tetradecenoylcarnitine (C14:1).…”
Section: Resultsmentioning
confidence: 99%
“…The design of this study has been previously reported. [13] Multiple gestation pregnancies and those ending in spontaneous/therapeutic abortions or intra-uterine fetal demise, as well as infants with HIV infection by positive DNA PCR testing at 6 weeks of life were excluded. During the study period, national guidelines for the Prevention of Mother-To-Child Transmission of HIV (PMTCT) underwent changes, reflecting updated WHO Guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations